Tracking physical breakdown of rice- and wheat-based foods with varying structures during gastric digestion and its influence on gastric emptying in a growing pig model. Issue 10 (22nd April 2021) - Nadia, Joanna; Olenskyj, Alexander G.; Stroebinger, Natascha; Hodgkinson, Suzanne M.; Estevez, Talia G.; Subramanian, Parthasarathi; Singh, Harjinder; Singh, R. Paul; Bornhorst, Gail M.
Abstract : Novel aspects of the work: Solid food macrostructure affects its physical breakdown processes in the stomach and gastric emptying rate. Abstract : There is currently a limited understanding of the effect of food structure on physical breakdown and gastric emptying of solid starch-based foods during gastric digestion. Moisture uptake, pH, particle size, rheological, and textural properties of six solid starch-based diets from different sources (Durum wheat and high amylose white rice) and of different macrostructures (porridge, native grain, agglomerate/couscous, and noodle) were monitored during 240 min of gastric digestion in a growing pig model. Changes in the physical properties of the gastric digesta were attributed to the influence of gastric secretions and gastric emptying, which were both dependent on the buffering capacity and initial macrostructure of the diets. Differences between the proximal and distal stomach regions were found in the intragastric pH and texture of the gastric digesta. For example, rice couscous, which had the smallest particle size and highest buffering capacity among the rice-based diets, had the shortest gastric emptying half-time and no significant differences between proximal and distal stomach digesta physical properties. Additionally, a relationship between gastric breakdown rate, expressed as gastric softening half-time from texture analysis, and gastric emptying half-time of dry matter was also observed. These findings provide new insights into the breakdown processes of starch-based solid foods in the stomach, which can be beneficial for the development of food structures with controlled rates of breakdown and gastric emptying during digestion.